Women and music in Ireland - Watson, Laura (Musicologist); Beausang, Ita; O'Connor-Madsen, Jennifer; Mullaney-Dignam, Karol; O'Donnell, Mary Louise; Lawlor, Helen; Kearney, Daithí; O'Donnell, Teresa; Klein, Axel; Engelhardt-Krajanek, M. (Margarethe) (Irish musical studies., 2022)
Explores the world of women's professional and amateur musical activity as it developed on and beyond the island of Ireland.